Analisis Pengaruh Kebijakan Pembatasan Loan to Value terhadap Return dan Risiko Saham Perbankan di BEI Tahun 2012-2013 - Purnama, Riony Rihardhika; Andati, Trias (Universitas Brawijaya, Indonesia, 2016)
Abstract: This studyis conducted on the basis of the implementation of monetary policy issued by Indonesia Bank for home loans. The main purpose of this research is to analyze the effect of policy implementation by Bank Indonesia on loan to value restriction to mortgages on June 15, 2012 and September 30, 2013 to the banking stock return, measured by abnormalreturn and risk premium. Data on this research is secondary data collected from Indonesian Stock Exchange. The sample is stock from 10 national banks that listed banks serving mortgage. Event study analysis is used to analyse the information content from the announcement, in combination with abnormal return as measurement indicator. This study finds that the policy implementation on September 30, 2013 has information content becausethere is significant difference between trading volume activity before and after the event but there is no significant difference between the average abnormal return before and after policy implementation on June 15, 2012 and September 30, 2013. GARCH in Mean model is used to analyse difference in the level of the risk premium after the policy implementationin 2012 and the implementation of policies in 2013. This study found as many as 6 of the 10 listed banks sampled showed a decrease in the coefficient of the risk premium as compared to coefficients of the risk premium in 2012.